2018
DOI: 10.1108/md-08-2017-0761
|View full text |Cite
|
Sign up to set email alerts
|

A cross-country comparison of green initiatives, green performance and financial performance

Abstract: Purpose The purpose of this paper is to investigate the relationship between green initiatives, green performance, and a firm’s financial performance in the world. The existing literature on environmental initiatives and their impacts is limited to the context of a particular country. This gap points to a lack of clarification of variations in environmental regulation and in economic disparity which may affect the impact of green initiatives on green performance and on financial performance. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 91 publications
6
30
0
2
Order By: Relevance
“…Announcement of the adoption of the ISO 14001 standards helps to gain a substantial positive effect on the stock values (Jacobs et al 2010). Chen et al (2018) also indicate a positive financial impact of green performances. Klassen and McLaughlin (1996) also show a positive effect of ISO 14001 certification on the valuation of the stocks.…”
Section: Prior Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Announcement of the adoption of the ISO 14001 standards helps to gain a substantial positive effect on the stock values (Jacobs et al 2010). Chen et al (2018) also indicate a positive financial impact of green performances. Klassen and McLaughlin (1996) also show a positive effect of ISO 14001 certification on the valuation of the stocks.…”
Section: Prior Literaturementioning
confidence: 98%
“…Secondly, the association between market performance and ISO 14001 is inconclusive and slightly mixed. Some researchers reported a positive association (Chen et al 2018;Flammer 2013;Jacobs et al 2010;Wahba 2010;Dowell et al 2000;Melnyk et al 2003;Klassen and McLaughlin 1996) while others found negative or weak associations (Lee et al 2008;Cañón-de-Francia and Garcés-Ayerbe 2009;King and Lenox 2001;Aarts and Vos 2001). Therefore, it is still unclear whether ISO 14001 enhances the market evaluation of the firms or not.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the growing ecological deterioration, sustainable development has emerged as noteworthy priority and a veritable challenge of our time (Alameeri, Ajmal, Hussain, & Helo, ; Ashraf et al, ; Melissen et al, ; Yarimoglu & Binboga, ). Consequently, in the hotel domain, environmental responsiveness is now steadily becoming a corporate issue (Chen, Ngniatedema, & Li, ; Chen, ; Kularatne et al, ). Therefore, hoteliers should address sustainability at all levels from policies formulation to final performance which is the criterion of achieving superior performance (Jenkins & Karanikola, ).…”
Section: Sustainability In Hotel Industrymentioning
confidence: 99%
“…However, as for hotel industry, the initial motivation to implement environmental activities was restricted up to cost saving through confining waste and energy usage (Alameeri et al, ). But, due to the rising demand for sustainable hotels, the successful implementation of sustainable initiatives has become not merely a cost saving activity but evenly related with guest expectations and demand for organizational image (Font et al, ; Chen et al, ). Even, environmental management superiority allows hotel to charge premium prices per room, increase sale by targeting potentially lucrative consumer segments, generate more cash, and so on (Leonidou et al, ).…”
Section: Sustainability In Hotel Industrymentioning
confidence: 99%
See 1 more Smart Citation